Analysis of the publicity of the VEJA magazine - Hernandes, Nilton (Laboratório Editorial FCL-UNESP, 2008)
This study aims to analyse one important publicity about Veja magazine e the mechanisms of production of meaning. We are interested about the values associated with the brand. The ad has three pages and was published in the magazine 30th anniversary edition. One of its main subject is the unemployment.